Holy Land, Whose Land - Zaineb lstrabadi (International Institute of Islamic Thought, 2003)
Dorothy Drummond's book was born at the dawn of the third millennium, when the author was in Jerusalem. She had taken notes throughout her travels in the Holy Land, which she defines not only as the land of historic Palestine, but also the lands of present-day Lebanon, Jordan, Syria, Iraq, and Egypt (i.e., where the Patriarchs, Prophets, and the Holy Family roamed). Rather than write a travelogue, she decided to write a book about the Arab-Israeli conflict while interspersing her personal comments (in italics) about her journeys. Her intent is not to "answer the question posed in the title of this book. Rather, by shedding light on dark corners, it attempts to bring understanding," as she explains in the prologue. The book is divided into three parts: a discussion of the IsraeliPalestinian conflict in the present, a discussion of the roots of the conflict traveling 4,000 years into the past, and a brief discussion of how negotiation is the only way to resolve the conflict. There are maps and pho tographs throughout the book, as well as a 40-page glossary of the Holy Land's people and places. Drummond has written the work in the present tense, because of the immediacy of all that has happened in the Middle East, but the discussion ultimately centers on the area between the Mediterranean Sea and the Jordan River. Her book promises to be a good, balanced account written in a wonwonderfully accessible style. However, early on it runs into problems. For example, when she talks about the 1956 Israeli attack on Egypt, she fails ...